Citizen awareness of plastic waste management and 3rs practices in urban Myanmar - Yadana Oo; Xue, Wenchao; Ekbordin Winijkul; Thi Phuoc Lai Nguyen; Asian Institute of Technology Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
The information and data from Myanmar was considered as outdated and far from the realist in past decades. The study on waste generation data was far more difficult to find from Myanmar. However, there are more and more research reports from NGOs like Thant Myanmar and IFF Myanmar are available on the waste generation and management system in Myanmar in late 2010s. Myanmar{u2019}s first National Waste Management Strategy and Master Plan (2018 {u2013} 2030) was published by ECD, MONREC with the support from CCET in 2018. NWMSMP set the 6 different goals with 3 different targets to achieve in 3 terms of period. However, there is no reference how those goals and timelines had been set on which database. This study focus on citizen awareness on current waste management facilities and knowledge on 3Rs. After survey questionaries were collected from 200 people from Mandalay and Yangon, the results shows the public awareness level in both city is higher than expected. Especially at the age group of 15 {u2013} 24 who were grown up under the democratic transitions with better interaction with social community engagement on environment and waste issues. To change the country with the better environmental governance, education is the significant variable which have effect on the level of awareness. But this study shows that the group with better education system have the higher level of awareness on 3Rs and environmental issues than those who have the higher education degree. The recommendation is provided to prove the results of the survey with developed ongoing waste management system country, South Korea where used to have the similar political changes.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Marine Plastics Abatement
Research studies project report (M.) - Asian Institute of Technology, 2021
Keywords: Plastics -- Environmental aspects -- Myanmar; Plastics industry and trade -- Waste disposal -- Myanmar; Plastic scrap -- Myanmar